Improving implementation of psychological interventions to older adult patients with cancer: Convening older adults, caregivers, providers, researchers. Issue 5 (September 2018) - Trevino, Kelly M.; Healy, Charlotte; Martin, Peter; Canin, Beverly; Pillemer, Karl; Sirey, Jo Anne; Reid, M. Cary
Abstract: Introduction: Older adults with cancer (OACs) are a large and growing population. Psychological distress is prevalent in this population yet few OACs receive evidence-based psychological care. The purpose of this project was to identify barriers and strategies for the implementation of psychological interventions to OACs from the perspective of OACs, OAC caregivers, researchers, clinicians, and advocacy organization members. Methods: The Cornell Research-to-Practice (RTP) Consensus Workshop Model was used to organize and convene a consensus conference. The one-day conference consisted of small and large group discussions regarding barriers, facilitators, and strategies for the implementation of psychological interventions targeting OACs. A half-day roundtable meeting was subsequently conducted to organize data generated at the conference. De-identified transcriptions of the small group discussions were uploaded into NVivo 11 software and qualitatively analyzed using standard methods. Results: Thirty-five participants attended the consensus conference from across stakeholder groups. Three themes related to implementation barriers were identified: lack of knowledge about psychological interventions in patients and providers; personal and social factors associated with being an OAC; and institutional-level factors. Themes related to implementation strategies focused on increasing awareness, tailoring interventions for older adults, and modifying institutional-level factors. Discussion: Effective implementation of psychological interventions to OACs is complex and barriers exist across multiple levels of care. However, this project indicates that implementation can be improved in various ways that include all members of the healthcare system. Further clarification of implementation strategies and rigorous evaluation of their effectiveness is vital to improving care and care outcomes of OACs.